STUDY OF THE INFLUENCE OF THE GRANULOMETRICAL COMPOSITION OF THE EXPLODED MASS ON THE EFFICIENCY OF THE EXCAVATION PROCESS IN THE DEVELOPMENT OF BUILDING ROCKS - SHVETS, YEHOR; HRYHORIEV, YULIAN; LUTSENKO, SERHII; KUKHAR, VOLODYMYR; FESENKO, EDUARD (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The purpose of the research is to analyze the degree of influence that rock mass fragmentation has on the productivity of loading equipment. To improve overburden removal operations and enhance the efficiency of excavation and loading equipment, the conditions for crushed stone quarry development were considered. The identification of research directions, which involves analyzing the current state of mining operations at quarries and reviewing literature on improving overburden removal processes under quarry conditions, allows for the formulation of goals and tasks related to the justification of a technological scheme for using cyclic equipment. An analysis was conducted on factors affecting the productivity of cyclic equipment in quarry faces. During the research, statistical methods were applied to process the results, and queuing theory was utilized for planning equipment productivity during shifts. The main focus of the study is on examining the impact of key drilling and blasting parameters on the quality of rock mass preparation, as well as the methods for calculating drilling and blasting parameters to achieve the required granulometric composition of the rock mass.